Helmintos de la República de Costa Rica V. Sobre la validez del género Controrchis Price, 1928 (Trematoda, Dicrocoeliidae ) y descripción de Controrchis caballeroi n. sp. - Jiménez-Quirós, Otto; Brenes, Rodrigo Ramón (Revista de Biología Tropical, 1957)
A further contribution is presented to the knowledge of the helminthologic fauna of Costa Rica, Central America, comprising : 1. Redescription of the genus Controrchis Price, 1928 (Trematoda, Dicrocoeliidae). 2. Description of a new species, Controrchis caballeroi, found in biliary ducts of Alouatta palliata palliata (Gray) Goodwin in Tilarán, province of Guanacaste, Costa Rica. 3. An histopathologic diagnosis of the presence of the trematode in biliary ducts of the host. 4. A chart of the specific differences between Controrchis biliophilus Price, 1928 and Controrchis caballero; n. sp. 5. A discussion of the validity of genus Controrchis and of the new species C. caballeroi.